Metachronous ileal cancer after surgery for ascending colon cancer in a patient with Lynch syndrome: A case report. (April 2021) - Tachikawa, Yuichi; Nozawa, Hiroaki; Hata, Keisuke; Abe, Hiroyuki; Ushiku, Tetsuo; Ishihara, Soichiro
Highlights: Few guidelines describe routine surveillance of small bowel cancer in Lynch syndrome. A male patient with Lynch syndrome underwent surgery for ascending colon cancer. Next year, metachronous cancer was found by colonoscopy inserted to the ileum. He survived disease-free for five years after resection of the ileal cancer. Our case suggested the importance of inspecting the small bowel in Lynch syndrome. Abstract: Introduction and importance: Colorectal surveillance via colonoscopy in patients with Lynch syndrome reduces the mortality of colorectal cancer. On the other hand, it is unclear whether surveillance for other malignancies, including small bowel cancer, is beneficial. We report a patient with Lynch syndrome who developed ileal cancer after surgery for ascending colon cancer. Case presentation: A 47-year-old man visited our hospital for a check-up for positive fecal occult blood. He was diagnosed with ascending colon cancer and met the clinical criteria for the diagnosis of Lynch syndrome based on his past and family history. The Bethesda markers demonstrated high-frequent microsatellite instability. Laparoscopy-assisted right hemicolectomy was performed. He received follow-up colonoscopy the next year, which revealed ileal cancer near the anastomosis. He underwent resection of the second cancer via a laparoscopic approach, and has been free from recurrence for five years. Clinical Discussion: Small bowel cancer has a dismal prognosis because a high percentage of patients were diagnosed at advanced stages. The diagnosis of metachronous ileal cancer by the first follow-up colonoscopy after surgery for ascending colon cancer offered a long disease-free survival in our patient. Conclusion: The clinical course suggested the importance of inspecting the small bowel in Lynch syndrome patients, especially when colorectal cancer is diagnosed.